Ethanol Disrupts Hormone-Induced Calcium Signaling in Liver. Issue 2 (8th January 2021) - Gaspers, Lawrence D; Thomas, Andrew P; Hoek, Jan B; Bartlett, Paula J
Abstract: Receptor-coupled phospholipase C (PLC) is an important target for the actions of ethanol. In the ex vivo perfused rat liver, concentrations of ethanol >100 mM were required to induce a rise in cytosolic calcium (Ca 2+ ) suggesting that these responses may only occur after binge ethanol consumption. Conversely, pharmacologically achievable concentrations of ethanol (≤30 mM) decreased the frequency and magnitude of hormone-stimulated cytosolic and nuclear Ca 2+ oscillations and the parallel translocation of protein kinase C-β to the membrane. Ethanol also inhibited gap junction communication resulting in the loss of coordinated and spatially organized intercellular Ca 2+ waves in hepatic lobules. Increasing the hormone concentration overcame the effects of ethanol on the frequency of Ca 2+ oscillations and amplitude of the individual Ca 2+ transients; however, the Ca 2+ responses in the intact liver remained disorganized at the intercellular level, suggesting that gap junctions were still inhibited. Pretreating hepatocytes with an alcohol dehydrogenase inhibitor suppressed the effects of ethanol on hormone-induced Ca 2+ increases, whereas inhibiting aldehyde dehydrogenase potentiated the inhibitory actions of ethanol, suggesting that acetaldehyde is the underlying mediator. Acute ethanol intoxication inhibited the rate of rise and the magnitude of hormone-stimulated production of inositol 1, 4, 5-trisphosphate (IP3 ), but had no effect on the size of Ca 2+ spikes induced by photolysis of caged IP3 . These findings suggest that ethanol inhibits PLC activity, but does not affect IP3 receptor function. We propose that by suppressing hormone-stimulated PLC activity, ethanol interferes with the dynamic modulation of [IP3 ] that is required to generate large, amplitude Ca 2+ oscillations. Graphical Abstract: